WORKING WITH STUDENTS AND ENSURING THEIR MEDIA AND INFORMATION LITERACY - Alimova Qunduz Oybek qizi (Journal of new century innovations, 2022)
Digital media is a central medium of activity and growth for young people, and media education is part of the everyday life of anyone working with youth. Media, digital technologies and youth media culture offer new perspectives and opportunities for working with young people. The Society for Media Education has prepared a kit to support media education work with young people, which aims to reveal the role of media education in working with young people and to provide tools for media education with young people. Aimed at providing Media use is an important part of the leisure time of young people, especially students. Therefore, it is natural to integrate media education into the process of working with young people. Working with young people means activities aimed at educating them outside the scope of formal education.